Bacterial Leaf Spot of Lettuce Disease: An Unpredictable Enemy to the Florida Lettuce Industry - German Sandoya; Dennis Calvin Odero (EDIS)
Bacterial leaf spot (BLS) of lettuce is caused by the bacterium Xanthomonas hortorum. BLS is more damaging in Florida, where the climate is conducive for disease development. The most effective control method is host resistance currently being developed by the UF/IFAS lettuce breeding program in all lettuce types. This new 4-page publication of the UF/IFAS Horticultural Sciences Department was written by Germán Sandoya and D. Calvin Odero.